Pembentukan Karakter Bertakwa Siswa melalui Kegiatan Tafakkur - Dewi Kusuma Ningrum, Sania; Agleo Putri, Indira; Rahmadina, Novvyta (Yayasan Darussalam Bengkulu, 2022)
This research focuses on efforts to improve the understanding of students at SD Negeri 106 Kota Bengkulu in being devoted to the One Almighty God and having noble character through Tafakkur activities. The main objective is to integrate religious values into daily activities, such as lectures and social activities with charitable nature. The action research method is employed, collecting data through observations and interviews with teachers and students. Data analysis reveals that a majority of students face difficulties in understanding Tafakkur due to their lack of seriousness in participating in the programs implemented at SD Negeri 106 Kota Bengkulu. To address this issue, an interactive learning approach and integration with other subjects are applied by teachers in the Tafakkur program, including interactive lectures and rewards to assist students in better understanding and being more enthusiastic during the Tafakkur program. The results of this implementation show a significant improvement in students' understanding of Tafakkur. This research concludes that interactive and contextual approaches play a crucial role in enhancing character and understanding of devotion among students, particularly in the context of Tafakkur.